DIAGNOSIS OF POST COVID-19 DISORDERS IN THE FUNCTION OF THE ENDOTHELIUM - Sviatoslav Ya. Kostiv; Ihor K. Venher; Boryslav P. Selskyi; Olga I. Kostiv; Andriy R. Vayda; Nazar I. Herasymiuk; Ihor I. Loyko (Клінічна та профілактична медицина, 2025)
Introduction. One of the characteristics of COVID-19, caused by the SARS-CoV-2 virus, is the broad, nonspecific nature of the pathological processes that develop in almost all organs and organ systems of the human body. At the same time, the development of endothelial dysfunction has been identified by many investigators as the pathological process that integrates these disorders and is considered the primary pathophysiological mechanism in severe cases.